2015
DOI: 10.4102/sajpsychiatry.v21i3.672
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent attachment, family functioning and depressive symptoms

Abstract: Background. Adolescence represents a challenging transitional period where changes in biological, emotional, cognitive and social domains can increase the risk of developing internalised problems including subthreshold depression. Adolescent-parent attachment style, perceived support and family functioning may increase risk for depressive symptoms or may reduce such risk. Adolescent-parent attachment, adolescentperceived support from parents and family functioning were examined as correlates of depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 14 publications
1
24
0
3
Order By: Relevance
“…Specifically, parent-adolescent attachment predicts the internalizing symptoms of depression. In particular, various studies have found significant associations between insecure parentadolescent attachment and depressive symptoms (Agerup et al, 2014;Constantine, 2006;DiFilippo & Overholser, 2000;Essau, 2004;Laible, Carlo, & Raffaelli, 2000;Rawatlal, Kliewer, & Pillay, 2015). Adolescents with insecure parent-adolescent attachment may feel incapable of being loved and may view their social environment negatively (Buirst, 2016;Sund & WichstrØm, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, parent-adolescent attachment predicts the internalizing symptoms of depression. In particular, various studies have found significant associations between insecure parentadolescent attachment and depressive symptoms (Agerup et al, 2014;Constantine, 2006;DiFilippo & Overholser, 2000;Essau, 2004;Laible, Carlo, & Raffaelli, 2000;Rawatlal, Kliewer, & Pillay, 2015). Adolescents with insecure parent-adolescent attachment may feel incapable of being loved and may view their social environment negatively (Buirst, 2016;Sund & WichstrØm, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, those with secure attachments have lower scores on measures of depression (Rice, 1990). Adolescents with secure attachments may have stronger emotional regulation skills because they are able to seek out their parents in times of need, protecting against the development of depressive symptoms (Rawatlal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found associations between higher levels of depressive symptomatology and insecure attachments between adolescents and their parents, while secure attachment was associated with a lower risk of developing depressive symptomatology in adolescence (Allen, Porter, McFarland, McElhaney, & Marsh, 2007;Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Duchesne & Ratelle, 2014;Rawatlal, Kliewer, & Pillay, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Attachment relationships are influenced by the quality of family functioning in terms of factors such as availability of support, cohesion, communication and levels of conflict (Rawatlal et al, 2015). In fact, the literature has shown that a positive relationship with parents, characterized by high support, cohesion, acceptance, affection, communication, and parental availability, has been associated with several positive development indicators, such as fewer problems of internalization, externalization and substance use, fewer risky sexual behaviours, better school performance, and better social skills (Branje, Hale, Frijns, & Meeus, 2010;Ewing, Diamond, & Levy, 2015;Kenny, Dooley, & Fitzgerald, 2013;Zhou, Sandler, Millsap, & Wolchik, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, os pais permanecem como figuras de vinculação importantes, sendo que a satisfação de necessidades relacionais na família, combinada com uma autonomia não excessiva, encontra-se associada a melhor ajustamento psicossocial (Levpušček, 2006). Estas relações de vinculação são influenciadas pela qualidade do funcionamento familiar que inclui fatores como a disponibilidade de suporte, coesão, comunicação e níveis de conflito (Rawatlal, Kliewer & Pillay, 2015). No âmbito da revisão de literatura, o presente estudo teve como objetivo estudar os efeitos preditores das estratégias de regulação emocional e da qualidade do relacionamento com os pais no desenvolvimento de sintomatologia depressiva em adolescentes portugueses.…”
Section: Introductionunclassified